PENGARUH AKSESIBILITAS DAN FASILITAS TERHADAP KUNJUNGAN WISATAWAN DI DESTINASI AJO MANENGGANG KECAMATAN SITIUNG KABUPATEN DHAMASRAYA - Maita Aulia; Rusydi Fauzan (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
Accessibility and facilities on tourist visits to the Ajo Manenggang tourist destination, Sitiung District, Dhamasraya Regency. The study is motivated by the damaged road access to this destination, and many of its facilities have not been completed yet, which has resulted in a fluctuation in the number of tourists who have come to this destination in the last five years. t-tests, determination tests, stimulus tests, and multiple linear regression tests are examples of hypothesis testing.  SPSS IBM version 22 is utilised for analysis.  The study's findings indicate that (1) accessibility significantly influences visitor numbers.  The computed t value > t table (2.811 > 1.985) demonstrates this.  0.007 is a significant value <0.05.  (2) Tourist visits are significantly impacted by facilities.  The calculated t value > t table (2.967 > 1.985) demonstrates this.  The Ajo Manenggang tourism site in Sitiung District, Dhamasraya Regency, is significantly impacted by both accessibility and facilities at the same time, with a significant value of 0.004 <0.05 (3).  The computed F value of 141.399 > F table value of 3.088 demonstrates this.  0.000 is a significant value less than 0.05.